\(I_2\)-Cauchy double sequences in 2-normed spaces - DÃ¼ndar, ErdinÃ§; Sever, Yurdal (Global Journal of Mathematical Analysis, 2014)
The concept \(I\)-Cauchy and \(I^*\)-Cauchy sequences were studied by Gudal and Acik in on \(I\)-Cauchy sequences in 2-normed spaces, Math. Inequal. Appl. 11 (2) (2008), 349–354. In this paper, we introduce thenotions of \(I_2\)-Cauchy and \(I_2^*\)-Cauchy double sequences, and study their some properties with (AP2) in 2-normed spaces.